Analisis Peubah Konsumsi pangan dan sosio ekonomi rumah tangga untuk menentukan indikator kelaparan - Ikeu Tanziha; Hidayat Syarief; Clara M Kusharto; Hardinsyah Hardinsyah; Dadang Sukandar (Media Gizi dan Keluarga, 2007)
ABSTRACT. The objective of the study was to analyze determinants of hunger. The study design was  a cross-sectional study. Research  was  conducted  in four  areas (Bogor Municipality,  Garut,  Karawang,  and  Pandeglang  Districts)  in  July-October  2003. A systematic stratified random  sampling was applied to select 400 households. The data collected included socio economic, perception on hunger, food expenditure and food intake. An Individual energy adequacy level was calculated by comparing actual intake to RDA (Recommended Dietary Allowances). Qualitatively, a person was categorized as hunger, if his/her daily meal portion and/or meal frequency decrease, along with body weight loss. The t-test and Mann-Whitney test were applied to analyse mean difference of socioeconomic, demographic and food intake variables between hunger and not hunger groups. Discriminant analysis was used to analyze indicators of hunger. There were mean difference of household head's education and mother's education, household expenditure percapita, and individual's food intakes between hunger and non hunger groups. Based on the discriminant analysis, main indicators of hunger in.this study area were rice consumption frequency and staple food expenditure ratio.A  Person was categorized  as hunger  if his or her rice consumption frequency < 14.76 times/ week or expenditure for staple food>23.15%